2018
DOI: 10.1007/s11604-018-0739-y
|View full text |Cite
|
Sign up to set email alerts
|

Imaging features of benign mass lesions in the nasal cavity and paranasal sinuses according to the 2017 WHO classification

Abstract: The World Health Organization (WHO) 2017 classification of head and neck tumors has been just published and has reorganized tumors of the nasal cavity and paranasal sinuses. In this classification, three new entities (seromucinous hamartoma, NUT carcinoma, and biphenotypic sinonasal sarcoma) were included, while the total number of tumors has been reduced by excluding tumors if they did not occur exclusively or predominantly in this region. Among these entities, benign tumors were classified as sinonasal papil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 59 publications
(82 reference statements)
0
34
0
1
Order By: Relevance
“…Our study showed just similar general MRI features. Still this retrospective review selected the lesions with striated pattern on T2 and post-contrast T1 images [26][27][28][29]. Though Yousem et al [30] stated that no signature pattern of MR imaging is specific of IP, later studies by Barnes et al…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed just similar general MRI features. Still this retrospective review selected the lesions with striated pattern on T2 and post-contrast T1 images [26][27][28][29]. Though Yousem et al [30] stated that no signature pattern of MR imaging is specific of IP, later studies by Barnes et al…”
Section: Discussionmentioning
confidence: 99%
“…246 An earlier World Health Organization document from 2017 addresses clinical characteristics and imaging findings of benign masses of the nose and sinuses. 247 Vasculitis, sarcoidosis, and other systemic diseases. The differential diagnosis of systemic diseases that can cause nasal symptoms is not included in this section; however, questioning for constitutional symptoms in all patients with rhinitis can be justified as a way to help exclude a systemic disease manifesting with rhinitis-type symptoms.…”
Section: Differential Diagnosis Of Rhinitismentioning
confidence: 99%
“…La aplicación de contraste revela una lesión heterogénea. En la resonancia magnética se observan lesiones heterogéneas con señal de intensidad baja a intermedia en T1 e intensidad alta a intermedia en T2 18 .…”
Section: Discussionunclassified